Antecedents of manic versus other first psychotic episodes in 263 bipolar I disorder patients. (10th July 2013) - Salvatore, P.; Baldessarini, R. J.; Khalsa, H.‐M. K.; Vázquez, G.; Perez, J.; Faedda, G. L.; Amore, M.; Maggini, C.; Tohen, M.
<x xml:space="preserve">Abstract</x> Objective As initial episode type can predict later morbidity in bipolar disorder, we tested the hypothesis that clinical antecedents might predict initial episode types. Method We studied 263 first‐episode, adult, DSM‐IV‐TR type I bipolar disorder (BD‐I) subjects within the McLean‐Harvard‐International First‐Episode Project. Based on blinded assessments of antecedents from SCID examinations and clinical records, we compared first lifetime manic vs. other (mixed, depressive, or non‐affective) major psychotic episodes. Results We identified 32 antecedents arising at early, intermediate or later times, starting 12.3 ± 10.7 years prior to first lifetime major psychotic episodes. Based on multivariate modeling, antecedents associated significantly and independently with other (n = 113) more than manic (n = 150) first lifetime major psychotic episodes ranked by odds ratio: more early attentional disturbances, more late depression, more early perplexity, more detoxification, more early unstable mixed affects, more antidepressants, more early dysphoria, more intermediate depression, more early impulsivity, more late anhedonia, longer early‐to‐intermediate intervals, more intermediate substance abuse, more family history of major depression, and younger at earliest antecedents. Antecedents selectively preceding manic more than other first psychotic episodes included more late behavioral problems and more risk of familial BD‐I. Conclusion Clinical antecedents in adult, BD‐I patients, beginning a decade before first major episodes and progressing through sequential stages were dissimilar in manic vs. other first psychotic episodes.